Conformational flexibility of dinucleoside dimers during unwinding from the B-form to an intercalation structure. - Malhotra, D (1980)
Intra-dinucleoside dimer conformational energy calculations were performed on a series of conformations corresponding to the unwinding of a dinucleoside dimer from the B-form type structure. Conformational states were characterized in terms of the distance, d, between parallel bases. All 16 possible sequences for (G) and (C) and/or (A) and (T) bases were considered. Both free space, and free space plus aqueous solvation energies were computed. It was found that the B-form like conformer is the most stable structures in free space and in an aqueous medium. However, the energy as function of d is base pair sequence dependent. This sequence dependence suggests a possible inherent specificity for intercalation of the dinucleoside dimer with a drug molecule.